Severe forms of fibromyalgia with acute exacerbation of pain: costs, comorbidities, and length of stay in inpatient care - Romeyke T; Noehammer E; Scheuer HC; Stummer H (Dove Medical Press, 2017)
Tobias Romeyke,1,2 Elisabeth Noehammer,1 Hans Christoph Scheuer,2 Harald Stummer1,3 1Institute for Management and Economics in Health Care, University of Health Sciences, Medical Informatics and Technology (UMIT), Hall in Tirol, Austria; 2Waldhausklinik Deuringen, Acute Hospital for Internal Medicine, Pain Therapy, Complementary, and Individualized Patient-Centered Medicine, Stadtbergen, Germany; 3Institute for Management and Innovation in Healthcare, University Schloss Seeburg, Seekirchen/Wallersee, Austria Background and purpose: As a disease of the musculoskeletal system, fibromyalgia is becoming increasingly important, because of the direct and indirect costs to health systems. The purpose of this study of health economics was to obtain information about staff costs differentiated by service provider, and staff and material costs of the nonmedical infrastructure in inpatient care.Patients and methods: This study looked at 263 patients who received interdisciplinary inpatient treatment for severe forms of fibromyalgia with acute exacerbation of pain between 2011 and 2014. Standardized cost accounting and an analysis of additional diagnoses were performed.Results: The average cost per patient was €3,725.84, with staff and material costs of the nonmedical infrastructure and staff costs of doctors and nurses accounting for the highest proportions of the costs. Each fibromyalgia patient had an average of 6.1 additional diagnoses.Conclusion: Severe forms of fibromyalgia are accompanied by many concomitant diseases and associated with both high clinical staff costs and high medical and nonmedical infrastructure costs. Indication-based cost calculations provide important information for health policy and hospital managers if they include all elements that incur costs in both a differentiated and standardized way. Keywords: fibromyalgia, DRG, cost, length of stay, comorbidities, interdisciplinary care, inpatient care, musculoskeletal, pain